Nonlinear associations between METS-IR and all-cause as well as cardiovascular mortality in adults with osteoporosis and osteopenia: evidence from NHANES 2007–2023 - Liu, Yazhou; Yang, Ying; Li, Yuhao; Ding, Wenbo; Yang, Xiaodong (Scientific reports, 2025)
Osteoporosis is a systemic metabolic bone disorder characterized by a decrease in bone mass and the degradation of bone microarchitecture. Nevertheless, the precise influence of the core marker of metabolic syndrome—insulin resistance—on the prognosis of patients with osteoporosis and osteopenia remains insufficiently understood. This study seeks to clarify the association between a novel insulin resistance metric, METS-IR, and the risks of all-cause and cardiovascular mortality among individuals diagnosed with OP. This study utilizes data from the National Health and Nutrition Examination Survey (NHANES) collected between 2007 and 2023, employing multivariable Cox proportional hazards regression models and restricted cubic splines to investigate the association between the METS-IR index and the risk of all-cause and cardiovascular mortality in patients diagnosed with osteoporosis and osteopenia. Furthermore, subgroup analyses were performed to identify potential effect modifications and high-risk subpopulations. The study cohort included 2175 individuals with osteoporosis and osteopenia, followed for 16 years, during which 468 all-cause deaths and 102 cardiovascular-related deaths were documented. The study identified a nonlinear positive association between the METS-IR index and the risks of all-cause mortality among patients with osteoporosis and osteopenia. However, no significant association was observed between METS-IR and cardiovascular mortality. At a METS-IR threshold of 2.3, the hazard ratio reached 1, indicating a shift in the risk of all-cause mortality from low to high. Furthermore, subgroup analyses demonstrated a stronger association between METS-IR and all-cause mortality risks in individuals with elevated METS-IR levels or comorbid diabetes, while no such significant relationship was found for cardiovascular mortality. This study highlights a nonlinear positive association between the insulin resistance marker METS-IR and all-cause mortality among patients with osteoporosis and osteopenia, whereas no significant association was observed with cardiovascular mortality. These findings enhance the understanding of insulin resistance’s role in osteoporosis and its comorbidities, particularly in relation to all-cause mortality. This underscores the importance of managing insulin resistance to improve overall survival outcomes, while further studies are needed to explore its specific impacts on cardiovascular outcomes.